Forum - - Add and subtract integers

# - Add and subtract integers

adding and subtracting integer

 *    adding two like signs integers is adding their distances from zero and preserving their sign 2 + 5 = 7         and      (-3) + (-10)  =  -13                                           *   adding two inlike signs integers is subtracting their distances from zero and preserving the sign of the one which has the great distance               (- 4) + 10 = 10 - 4 = 6                and                   15 + ( - 20 ) = - ( 20 - 15 ) = - 5      *     the addition of two opposite number is equal to   zero                                                                                                                                                                                                                                                              ( - 6) + 6 = O                                                                                                                   *     to subtract two integers we add to the first the opposit of the second                                                                            (-6 ) - 8 = (-6) + (-8) = - 14

examle1

5+(-2)  =

(-5) +2  =

5+2  =

(-5)+(-2)   =

example

(-5) +8

exercise1

(-6) - (-4)=

(-5) + 3=

12 )- (-8)=)

-15 - (5))

(-2) + (-7)=

4 7=

adding and subtracting with branckets

rule

 *  you can remove the bracket after the sign (+) in condition to change all signs of numbers inside the bracket                                                                *  you can remove the bracket after the sign (-) without   changing  the signs of numbers inside the bracket                                                                        rules a - ( b + c ) = a - b - c a - ( b - c ) = a - b + c  a + ( b + c ) = a + b + c a + ( b - c ) = a + b - c

examples

 −(−x + y) = x − y.
 −(x − y) = −x + y.
 .   −(x + y − 2) = −x − y + 2.

 a − [b − (c − d + e)] = a − [b − c + d − e] = a − b + c − d + e.

exercises

remove the brackets then simplify

 (x − 3) − (y − 4) =
 (x + 2) + (y + 8) =
 (x + 2) − (y + 8) =
 .  (x − 2) + (y + 8) =
 .  (x − 2) − (y + 8) =
 .  (x − 2) − (y − 8)=
 .  (x − 2) + (y − 8)=
 .  (a − 2) + (b + 3) − (c − 7)=

 (a − 5) − (b + 6) − (c − 9) =
 (a + 2) − (b − 3) + (c − 8) − (d + 1)=